(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2019)
The black cutworm Agrotis ipsilon (Lepidoptera: Noctuidae) is a polyphagous pest that attacks more than one hundred types of crops. The habit of being buried or underneath the cultural remains may help contact with entomopathogenic nematodes (EPNs), which are natural enemies of insects. The objective of this study was to evaluate the persistence of the pathogenicity of Steinernema carpocapsae and S. feltiae (Rhabditida: Steinernematidae) applied to the soil against A. ipsilon larvae. The EPNs were applied to vases containing soil and larvae of A. ipsilon were introduced into the pots in five periods (0, 2, 4, 6, and 8 days after treatment). The two species of EPNs caused pathogenicity in all evaluated periods. The mortality rate was over 92% in all treatments and periods.